THE EXPERIMENTAL STUDY CONCERNING THE IMPROVING OF THE VERTICAL DETACHEMENT OF THE NINTH CLASS STUDENTS - USING THE SPECIFIC BASKETBALL GAME MEANS - Mirela Gheorghiţă Solcan; Virgil Larionescu Moroşan (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2018)
The force is a dynamics quality, highly complex and rather nondescript. The expansion is a force manifestation and it is defined as the ability of muscle groups to develop maximum strength in a short time, strength-speed. This paper aims to emphasize if the development methods and means of specific basketball play, of the combined dynamics quality, the expansion at flashing legs level, in ninth class students, have application and are effective in the basketball game. Acting on students, by means of the basketball game, of attack through shooting from dribbling, it take place a higher load of the musculature, that develops in parallel, the force muscle and speed in ankle, knee and hip femoral articulations.